PERANAN KEPALA DESA DALAM MENINGKATKAN ADMINISTRASI KEPENDUDUKAN PADA KANTOR DESA PONGAN KECAMATAN BOKAT KABUPATEN BUOL - Dunggio, Rusli (STISIPOL Mujahidin Buol, 2022)
Administration is interesting to research because judging from the origins characteristics and problems that occur in the Pongan village office, Bokat District, as the lowest government organization about autonomy, the autonomy possessed by the village is based on rights, so to know the leadership role of the village head in village office administrative services. Pongan, Bokat District, KTP Family Card Birth Certificate service. This research aims to determine the role of the village head in population administration services at the Pongan village office, Bokat District, Buol Regency. This research uses descriptive qualitative methods. The data sources used are primary data and secondary data, with data collection techniques through observation, interviews, and documentation. Meanwhile, the data analysis technique used is Milles and Huberman. The results of the research show that the role of the Village Head in Population administration services at the Poongan Village Office, Bokat District in the areas of Population Identification Card, Family Card, and Birth Certificate Issuance services has been carried out well by the community's expectations.